Drink, Share, and Comment; Wait, What Did I Just Do? Understanding Online Alcohol-Related Regret Experiences Among Emerging Adults. (July 2021) - Geusens, Femke; Vranken, Ilse
This study investigated the causes and coping strategies of regret of sharing alcohol-related content on social media. Semi-structured interviews were conducted among emerging adults who experienced regret of having shared either general alcohol references or drunken references ( n = 29, ages 19–25 years, M = 21.38, SD = 1.60). The most important cause of regret was a disruption of one's online self-presentation. When delving deeper into the specific causes of online alcohol-related regret and how this content can disrupt the self-presentation, two overarching themes emerged: (a) content-related regret, and (b) audience-related regret. When examining the coping strategies, we found that emerging adults applied different strategies (a) to minimize their regret (e.g., delete the content), and (b) to avoid future regret (e.g., delete social media before going out). Implications for prevention are discussed.